INNOVATIVE LEADERSHIP IN AGRICULTURE: TRANSFORMING FARM RESOURCES INTO INNOVATIVE RURAL PRODUCTS – THE CASE OF TUSCANY - Ignjatović P., Aleksandar; Vujko, Aleksandra; Zimonjić, Marijana (Economics of Agriculture, 2026)
Agricultural systems are increasingly shifting fromproduction-oriented models toward diversified andmarket-integrated structures, requiring new approachesto value creation. The purpose of this study is to examinehow leadership influences the transformation of farmresources into innovative and market-relevant outputs.The research is based on survey data collected from 488farm owners and agricultural entrepreneurs in Tuscany,and the relationships among constructs were analyzedusing a structural modeling approach. The results showthat visionary leadership significantly drives resourcetransformation and innovation, while innovationorientation represents the strongest predictor of marketintegration. Resource transformation also contributesdirectly and indirectly to market outcomes throughinnovation processes. The findings indicate that valuecreation in agriculture follows a sequential pathwaylinking leadership, resources, innovation, and markets.The study concludes that leadership is a key mechanismin enhancing farm competitiveness and sustainability. Itis recommended that farm managers and policymakerssupport leadership development, resource diversification,and innovation-oriented strategies in rural areas.